The frontcrawl downsweep: shoulder protection and/or performance inhibition - Clarys, J. P.; Rouard, A. H. (The Journal of Sports Medicine and Physical Fitness, 1996)
EMG of 6 shoulder and arm muscles was measured in nine good frontcrawl swimmers using active electrodes and a telemetric EMG data acquisition system. The raw EMG was low pass filtered, rectified and the integrated values were used as a measure of muscular intensity. The selection of muscles combined 2 mono-articular and 2 bi-articular shoulder muscles and 2 muscular primarily acting on elbow & wrist. Kinematic analysis allowed for a detailed time and movement pattern fractionation and the muscle activity within these phases was analysed for 4 x 100 m at maximum effort up to exhaustion. The combination of time distribution and muscular activity suggested that the downsweep is the longest in time but with the lowest intensity of all 4 transient phases of the cyclic arm movement. This is assumed to be effective for decreasing the load of the shoulder joint. However, it could also be considered that if the insweep with its higher muscular participation could start earlier in the pull phase while shortening the downsweep. The higher, but more constant loading of the shoulder might improve performance.